2018
DOI: 10.2478/raon-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance metabolic fingerprint of bevacizumab in mutant IDH1 glioma cells

Abstract: BackgroundMalignant gliomas are rapidly growing tumours that extensively invade the brain and have bad prognosis. Our study was performed to assess the metabolic effects of bevacizumab on the glioma cells carrying the IDH1 mutation, a mutation, associated with better prognosis and treatment outcome. Bevacizumab is known to inhibit tumour growth by neutralizing the biological activity of vascular endothelial growth factor (VEGF). However, the direct effects of bevacizumab on tumour cells metabolism remain poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition, Fack et al [ 48 ] also reported the down-regulation of the γ-glutamyl cycle and a reduction in all associated metabolites, including cysteine, glutamate, glycine, and glutathione [ 48 ]. Most of the above-mentioned findings were confirmed in mutant IDH1 glioma cells by Mesti et al [ 47 ], who found significant changes not only in the metabolites from the glutamine group (e.g., glutamate, alanine, and glycine) but also in the lipids. In this work, Mesti et al observed modified levels of polyunsaturated fatty acids (PUFA), glycerophosphorylcholine (GPC), and phosphatidylcholine (PC) following bevacizumab treatment and considered these changes early markers of metabolic alterations due to this treatment [ 47 ].…”
Section: Immune Therapy—monoclonal Antibodiesmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, Fack et al [ 48 ] also reported the down-regulation of the γ-glutamyl cycle and a reduction in all associated metabolites, including cysteine, glutamate, glycine, and glutathione [ 48 ]. Most of the above-mentioned findings were confirmed in mutant IDH1 glioma cells by Mesti et al [ 47 ], who found significant changes not only in the metabolites from the glutamine group (e.g., glutamate, alanine, and glycine) but also in the lipids. In this work, Mesti et al observed modified levels of polyunsaturated fatty acids (PUFA), glycerophosphorylcholine (GPC), and phosphatidylcholine (PC) following bevacizumab treatment and considered these changes early markers of metabolic alterations due to this treatment [ 47 ].…”
Section: Immune Therapy—monoclonal Antibodiesmentioning
confidence: 67%
“…Most of the above-mentioned findings were confirmed in mutant IDH1 glioma cells by Mesti et al [ 47 ], who found significant changes not only in the metabolites from the glutamine group (e.g., glutamate, alanine, and glycine) but also in the lipids. In this work, Mesti et al observed modified levels of polyunsaturated fatty acids (PUFA), glycerophosphorylcholine (GPC), and phosphatidylcholine (PC) following bevacizumab treatment and considered these changes early markers of metabolic alterations due to this treatment [ 47 ]. The identification of biochemical pathways affected by bevacizumab enables the proposition of potentially effective combination therapies.…”
Section: Immune Therapy—monoclonal Antibodiesmentioning
confidence: 67%
“…Although the authors attributed this effect to temrolimus, our results suggest that VEGF inhibition alone can increase serum lipid concentrations. In vitro studies with different glioma cell lines have also demonstrated increased levels of fatty acids and changes in choline metabolism after pharmacological treatment with VEGF receptor 2 inhibitor or with bevacizumab [30], [31]. Overall, similar metabolic alterations have also been associated with increased apoptosis in several cell lines [30], [31], [32], [33], [34].…”
Section: Discussionmentioning
confidence: 94%
“…In vitro studies with different glioma cell lines have also demonstrated increased levels of fatty acids and changes in choline metabolism after pharmacological treatment with VEGF receptor 2 inhibitor or with bevacizumab [30], [31]. Overall, similar metabolic alterations have also been associated with increased apoptosis in several cell lines [30], [31], [32], [33], [34]. Although aflibercept does not appear to overtly induce apoptosis in cell models [35], [36], [37], [38], the metabolic shifts observed in our study could reflect aflibercept-mediated in vivo tissue hypoxia and oxidative stress that drive apoptotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Most cell-line studies are conducted in the domain of defining metabolomic profiles or testing treatment efficacy for various malignant and nonmalignant diseases. 40,[136][137][138][139][140][141][142][143][144][145][146][147][148] In addition, a number of studies have used HRMAS NMR to investigate cell structures and real-time metabolic reactions.…”
Section: Metabolomics Studies Of Cellsmentioning
confidence: 99%